Temperature and stress dependent twinning behavior in a fully austenitic medium-Mn steel. (1st June 2022) - Magagnosc, D.J.; Field, D.M.; Meredith, C.S.; An, K.; Walter, T.R.; Limmer, K.R.; Lloyd, J.T.
Graphical abstract: Abstract: In this study in situ neutron diffraction investigations of a fully austenitic medium-Mn steel enabled key insights into the temperature dependence of the deformation response with a focus on twinning. In situ tensile loading at multiple temperatures enabled the calculation of the temperature and strain dependence of the effective stacking fault energy (SFE), which was compared with theoretical SFE calculations and ex situ tensile tests. These comparisons revealed that the γ -austenite/ ϵ -martensite interfacial energy plays a critical role in determining the boundary between twinning and transformation induced plasticity. The interfacial energy, which also exhibits temperature dependence, was found to be lower than the conventionally accepted range for medium-Mn steels deforming via twinning. Dynamic strain aging (DSA) was also found to impact the deformation response. DSA contributes to increasing the separation of partial dislocations, which in turn lowers the effective SFE and was observed as fluctuations in the measured SFE when DSA was active. The additional extrinsic contributions to the SFE from DSA, which operates over a limited range of temperatures and strain rates, has not previously been accounted for.